The giant is threatened: narratives of hatred and radicalism in Brazil 2018 - Carnieletto Müller, Angelo (Rizoma, 2020)
This paper addresses the perceived polarization climate between opposers and supporters of the former PT government, before the 2018 presidential campaign, to understand how its discourses manifested through the media, and if it can be related to the eruption of political violence. By Content Analysis, the study features four relevant happenings in recent Brazilian political history, revealing the language of contention (Tilly & Tarrow, 2015) between politicians, and also in the mainstream media. Drawing from Benoit’s Functional Theory of Political Campaign Discourses (2007), we found that hatred and polarization have been the common ground in Brazilian politics, and tested two frameworks for the eruption of political violence (Harff, 2003; Benesh, 2010), providing an understanding of the immediate threats that linger over the country’s democracy.